An overview of the urbanism style during the Italian era in Benghazi downtown, Libya - Eltrapolsi, Ali (Journal of Architecture and Urbanism, 2022)
Axiomatically, urban fabric is the result of civilizations and ideas overlapping rather than being bound to a single civilization or culture. Benghazi, like many other Arab cities in developing countries, retains relics of its past in the old city core. This urban fabric’s visual character is created by reflecting the underlying cultural background, practices, beliefs, and climatic conditions in its content. Therefore, it is necessary to assess the concepts that have been used to develop Italian urbanism before trying to rebuild the damaged urban fabric. This study presents the urban pattern of old Benghazi in order to understand the values inherited from the past and the impact of the Italian urban expansion. A second part of the research provides an overview of the extension of the urban fabric, starting from the Italian square, located within the old city. As a final point, the discussion and conclusion presented the concept and relationship of formations in Italian architecture that achieve a unique transition by experiencing architectural principles, their basic components, and their comfortable surroundings at the moment.